New Inner Product Quasilinear Spaces on Interval Numbers - Hacer Bozkurt; Yılmaz Yilmaz (Journal of Function Spaces)
Primarily we examine the new example of quasilinear spaces, namely, “IRn interval space.” We obtain some new theorems and results related to this new quasilinear space. After giving some new notions of quasilinear dependence-independence and basis on quasilinear functional analysis, we obtain some results on IRn interval space related to these concepts. Secondly, we present Is,Ic0,Il∞, and Il2 quasilinear spaces and we research some algebraic properties of these spaces. We obtain some new results and provide an important contribution to the improvement of quasilinear functional analysis.